Recent Publications (Quarterly Journal of Economics, 1947)
Recent Publications Get access The Quarterly Journal of Economics, Volume 62, Issue 1, November 1947, Pages 160–163, https://doi.org/10.1093/qje/62.1.160 Published: 01 November 1947